2016
DOI: 10.1137/15m1023191
|View full text |Cite
|
Sign up to set email alerts
|

Imaging with Power Controlled Source Pairs

Abstract: Scatterers in a homogeneous medium are imaged by probing the medium with two point sources of waves modulated by correlated signals and by measuring only intensities at one single receiver. For appropriately chosen source pairs, we show that full waveform array measurements can be recovered from such intensity measurements by solving a linear least squares problem. The least squares solution can be used to image with Kirchhoff migration, even if the solution is determined only up to a known one-dimensional nul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Thus, we have computationally generated the data for exactly the same microspheres as we have used in experiments. We have observed that computational results for the forward problem have a very good similarity with experimental data, see Figures 4,5,8. In addition, inversion results for both experimental data sets are very similar with the those of computationally simulated data, see Figures 6,7,9 and Tables 1,2. Finally, the reconstruction error of the refractive index is between 5.2% and 5.4% in all cases, which is small.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Thus, we have computationally generated the data for exactly the same microspheres as we have used in experiments. We have observed that computational results for the forward problem have a very good similarity with experimental data, see Figures 4,5,8. In addition, inversion results for both experimental data sets are very similar with the those of computationally simulated data, see Figures 6,7,9 and Tables 1,2. Finally, the reconstruction error of the refractive index is between 5.2% and 5.4% in all cases, which is small.…”
Section: Discussionsupporting
confidence: 58%
“…We now refer to other approaches to phaseless inverse scattering problems. In [7,8] a phaseless CIP for Helmholtz equation was solved numerically using Kirchhoff migration and Born approximation. While coefficients of partial differential equations are subjects of interests in all above cited works, there is also a significant interest in the reconstruction of surfaces of scatterers from the phaseless data.…”
Section: Introductionmentioning
confidence: 99%
“…Uniqueness theorems were proved and reconstruction procedures were proposed in [44][45][46]. In [6,7] a phaseless coefficient inverse scattering problem for Helmholtz equation was solved numerically using Kirchhoff migration and Born approximation. While coefficients of PDEs are subjects of interests in the above cited works, there is also a significant interest in the reconstruction of surfaces of scatterers from phaseless data.…”
Section: Introductionmentioning
confidence: 99%
“…Proposition 5 is the electromagnetic analogue of a statistical stability result for scalar waves that was proven originally in [28] (see also [8]) and is proved in Appendix A.…”
Section: The Coherency Matrix From Time Domain Electric Field Autocor...mentioning
confidence: 72%
“…A key aspect of our imaging method is that we do not need to retrieve all phases from the data, since the imaging method we use does not require it. This is a feature that is also used for intensity only imaging in [8,9,[40][41][42]. For full aperture data, phase retrieval is done in [21][22][23] using a similar preprocessing of the intensity data as we present here.…”
Section: Related Workmentioning
confidence: 99%